O desencantamento do mundo: uma reflexão necessária para o ensino de ciências e matemática - Araújo, Elian Sandra Alves de (2013)
In this work we intend to reflect on some possible meanings for the expression 'disenchantment of the world'. When these positions assume extremes, they are not recommendable, because the act of demonizing or divinize the advent of science and technology restricts the real complexity involved in both: as regards the scientific achievements as with regard to its impact on modern life. We argue that a constructive and open dialogue involving a gradation of positions constitutes something more advisable to guide a critical science education for the citizen. We proceed to a confrontation between a worldview guided by free imagination that knows no limitations of the laws of the natural world with a vision of the world that is governed by these laws. In order to do that, we implement a confrontation between the texts of Galileo (1935), with the narratives of Jonathan Swift (1978) and Monteiro Lobato (1968). We emphasize that a scientific education that engenders a genuine formation for the citizen must be based on the complementarity between the two worldviews, since this should be considered as essential to the realization of the Teaching of Science and Mathematics in their current perspective.